Fast optical preparation, control, and readout of a single quantum dot spin - Ramsay, A. J.; Boyle, S. J.; Kolodka, R. S.; Oliveira, J. B.B. [UNESP]; Skiba-Szymanska, J.; Liu, H. Y.; Hopkinson, M.; Fox, A. M.; Skolnick, M. S. (American Physical Society (APS), 2008)
We propose and demonstrate the sequential initialization, optical control, and readout of a single spin trapped in a semiconductor quantum dot. Hole spin preparation is achieved through ionization of a resonantly excited electron-hole pair. Optical control is observed as a coherent Rabi rotation between the hole and charged-exciton states, which is conditional on the initial hole spin state. The spin-selective creation of the charged exciton provides a photocurrent readout of the hole spin state. © 2008 The American Physical Society.